2022
DOI: 10.3390/ijerph19042111
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Occupational Health Risk Perception on Job Satisfaction

Abstract: This study explored the relationship between occupational health risk perception and job satisfaction. Based on the job demand-resources model and resource conservation theory, eight hypotheses were proposed in this study. In a survey of 237 production line workers and managers, we found that perceived occupational health risks significantly negatively affected job satisfaction. Both work stress and organizational commitment mediate the relationships between perceived occupational health risks and job satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 49 publications
1
17
0
5
Order By: Relevance
“…For SMEs, employees are their core assets and are crucial to their survival and growth (Shan et al, 2022 ). Employee work stress may precipitate burnout (Choi et al, 2019 ; Barello et al, 2020 ), which manifests as fatigue and frustration (Mansour and Tremblay, 2018 ), and is associated with various negative reactions, including job dissatisfaction, low organizational commitment, and a high propensity to resign (Lu and Gursoy, 2016 ; Uchmanowicz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For SMEs, employees are their core assets and are crucial to their survival and growth (Shan et al, 2022 ). Employee work stress may precipitate burnout (Choi et al, 2019 ; Barello et al, 2020 ), which manifests as fatigue and frustration (Mansour and Tremblay, 2018 ), and is associated with various negative reactions, including job dissatisfaction, low organizational commitment, and a high propensity to resign (Lu and Gursoy, 2016 ; Uchmanowicz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the study of Shan et al [ 62 ], the process of developing the questionnaire is shown as follows: First, several employees from different companies were interviewed. This step let us understand more about the core concepts of this study, including job performance and employees’ mental health.…”
Section: Methodsmentioning
confidence: 99%
“…Jahangiri et al (2013) described risk perception as "an individual's subjective judgment about the characteristics and severity of risks". Risk perception is one of the characteristics of a person that affects an individual's behaviour, so a misperceived risk leads to insecurity in the workplace; therefore, investigating risk perception plays an important role in ensuring workplace safety (Jafari et al, 2019) and individual work output (Shan et al, 2022;Szydło & Grześ-Bukłaho, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%